Role of chimerism versus immunosuppressive drug therapy in kidney transplant survival: Scoping Review - Baquero-Tabares, Laura (2021)
Aim: To compare the efficacy of chimerism with immunosuppressive drug therapy for kidney transplant survival. Materials and methods: A systematic search of the literature was carried out in Medline, using the PRISMA statement guidelines and the MeSH-type health descriptors. The criteria used for the selection of articles were studies conducted in humans, in English or Spanish and published between 1995 and 2020. Results: Twenty-two articles published between 1995 to 2020 were included. The majority of studies used some cytoreductive conditioning regimen prior to combined kidney and hematopoietic stem cell transplantation. For chimerism, the majority achieved a mixed or complete chimeric state. The average of immunosuppressive drug withdrawal after renal and hematopoietic stem cell transplantation was 2.4 months, and was maintained for 4 to 55 months, with satisfactory recovery of renal function and no evidence of rejection episodes. Finally, 22 articles included in this review concluded that chimerism has a role in inducing immune tolerance that improves kidney survival in patients undergoing kidney transplantation. Conclusions: Mixed chimerism induces immunological tolerance that translates into stable kidney function, lower rejection rates, and longer kidney graft survival, without the need for maintenance immunosuppressive therapy.